A alienação no Porto : o Hospital de Alienados do Conde de Ferreira (1883-1908) - Pereira, Pedro Teixeira; Gomes, Eva; Martins, Olga (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Despite the fact that the Hospital de Alienados do Conde de Ferreira no longer assumes the same purposes for which it was created in the past, its importance and age-old prominence still prevail. Thus, this paper seeks to understand and analyze the Portuguese model of hospital assistance for the demented at the turn of the 19th century, based on the study of the services provided at the Hospital do Conde de Ferreira. We feel that it is particularly pertinent to determine to what extent this Hospital applied the scientific modernity of this period.